The Effect of Sun Exposure on the Severity Degree of Photoaging and Skin Hydration on Service Workers at dr. Zainoel Abidin Regional General Hospital Banda Aceh - Wahyu Lestari; Dinda Ayu Puspita; Muhammad Mizfaruddin; Sitti Hajar (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Photoaging is the aging of the skin characterized by the appearance of wrinkles, telangiectasis, solar elastosis, pigmentation and keratosis. Photoaging is usually caused by external factor, such as sun exposure. The radiation from the sun causes an increase of the reactive oxygen species (ROS). Cell damage, dry skin, photoaging, and skin cancer are all caused by the accumulation of ROS in the skin. Purpose: The goal of this study is to find out how sun exposure affects the severity of photoaging and skin hydration at dr. Zainoel Abidin Regional General Hospital Banda Aceh. Methods: This is an analytic observational study with an accidental sampling technique. Sun exposure was measured by a questionnaire, the severity of photoaging was assessed based on the doctor's diagnosis, and skin hydration was assessed through an examination using a corneometer and tewameter. Results: This study indicates that there is an effect of sun exposure and the severity of photoaging with p value of 0.016, while skin hydration shows a significant effect of sun exposure on hydration with a corneometer parameter with a p value of 0.031 Conclusion: There is a substantial correlation between sun exposure and the severity of photoaging. There is a substantial relationship between sun exposure and skin moisture, as measured by the corneometer parameter.